HUBUNGAN DUKUNGAN SPIRITUAL DENGAN PSYCHOLOGICAL WELL BEING PADA LANSIA DI PUSKESMAS LAMPISANG KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR - Fadillah, Fitriani; Zuidah, Zuidah; Purba, Widya Darayani (Indonesian Trust Health Journal, 2025)
Getting old or aging is a condition that occurs in human life. Along with increasing age. Spiritual support refers to all forms of assistance given to individuals in meeting their spiritual needs. The purpose of this study was to determine the relationship between spiritual support and psychological well-being in the elderly in the fostered area of ​​the Lampisang Health Center, Peukan Bada District, Aceh Besar Regency. type of descriptive correlational research, with a cross-sectional design. The population of all elderly living in the fostered area of ​​the Lampisang Health Center, Peukan Bada District, was recorded as many as 120 elderly in February 2025. The purposive sampling technique was in accordance with the criteria desired by the researcher as many as 25 elderly people. The results obtained were that the majority of elderly spiritual support was moderate as many as 13 people (52%), and the majority of elderly psychosocial well-being was moderate as many as 15 people (60%). The results of the hypothesis test showed that the majority of elderly spiritual support was moderate as many as 13 people (64%) with moderate psychological well-being as many as 8 people (32%). The results of the statistical test with chi square with a value of 0.001 (<0.05) means that there is a Relationship between Spiritual Support and Psychological Well Being in the Elderly in the Area of ​​the Lampisang Health Center, Peukan Bada District, Aceh Besar Regency. The conclusion of the study is that there is a Relationship between Spiritual Support and Psychological Well Being in the Elderly in the Area of ​​the Lampisang Health Center. It is recommended that the head of the local health service improve the standard of service and quality in providing nursing care services in the community, especially for the elderly. Abstrak Menjadi tua atau menua adalah suatu keadaan yang terjadi di dalam kehidupan manusia. Seiring dengan bertambahnya usia. dukungan spiritual mengacu pada segala bentuk bantuan yang diberikan kepada individu dalam memenuhi kebutuhan spiritualnya. Tujuan dalam penelitian ini adalah Untuk Mengetahui Hubungan Dukungan Spiritual dengan dengan Psychological Well Being Pada Lansia di Wilayah Binaan Puskesmas Lampisang Kec. Peukan Bada Kab. Aceh Besar. jenis penelitian deskriftif korelasional, dengan desain cross sectional. Yang menjadi populasi seluruh Lansia yang tinggal di Wilayah Binaan Puskesmas Lampisang Kec. Peukan Bada, tercatat sebanyak 120 lansia pada Bulan Februari 2025. Teknik pengambilan sampel Purposive Sampling sesuai dengan kriteria yang dikehendaki peneliti sebanyak 25 orang lansia. Hasil yang didapatkan dukungan spiritual lansia mayoritas sedang sebanyak 13 orang (52%), dan Psikososial Well Being pada lansia mayoritas sedang sebanyak 15 orang (60%). Hasil uji hipotesis mayoritas dukungan spiritual lansia sedang sebanyak 13 orang (64%) dengan psikologikal well being sedang sebanyak 8 orang (32%). Hasil uji statistik dengan chi square dengan nilai Value sebesar 0.001 (< 0.05) artinya ada Hubungan Dukungan Spiritual dengan dengan Psychological Well Being Pada Lansia di Wilayah Binaan Puskesmas Lampisang Kec. Peukan Bada Kab. Aceh Besar. Kesimpulan penelitian ada Hubungan Dukungan Spiritual dengan dengan Psychological Well Being Pada Lansia di Wilayah Binaan Puskesmas Lampisang. Disarankan kepala pelayanan kesehatan setempat agar dapat meningkatkan standart pelayanan dan kualitas dalam pemberian pelayanan asuhan keperawatan diranah komunitas khususnya pada lansia.